Management of equivocal (early) Fournier’s gangrene - Mohamed El-Shazly; Mohamed Aziz; Hamdy Aboutaleb; Shady Salem; Eid El-Sherif; Mohamed Selim; Mohamed Sultan; Mohamed Omar; Tarek Abd Elbaky; Fouad Zanaty; Talal Alenezi; Abdelazeem Ghobashi; et al. (Therapeutic Advances in Urology, 2016)
Background: Fournier’s gangrene (FG) is an acute progressive necrotizing fasciitis of the genital area and perineum with possible extension to the abdominal wall. Surgical debridement is the gold standard management modality of established patients. Equivocal (early) FG represents a challenge in diagnosis. The objective of this study was to compare conservative management and early exploration in cases of equivocal (early) FG. Methods: This was an observational study where data of all patients diagnosed as early FG in our departments over 4 years (2011–2015) were enrolled. Patients were divided into two groups: group 1 with conservative treatment, and group 2 managed with urgent exploration with longitudinal hemiscrotal incision starting from external inguinal ring. All patients’ demographics, vital signs, laboratory finding and clinical findings were reported. Results: A total of 28 patients were enrolled in the study. Group 1 was managed with conservative treatment (17 patients) and group 2 underwent urgent exploration (11 patients). Overall, four patients (23.5%) out of 17 patients of group 1 showed a good response to conservative management without any surgical debridement. A total of 13 patients (76.5%) developed gangrenous discoloration and needed surgical debridement later. In group 2, four patients (36.4%) underwent scrotal exploration and release incision only without debridement and showed an excellent clinical outcome. A total of four patients (36.4%) underwent debridement with excision of doubtful deep subcutaneous and fascial tissues. The remaining three patients (27.2%) underwent debridement of necrotic fascia. The hospital stay was significantly shorter in group 2 patients than group 1 (7.5 ± 3.75 versus 13.4 ± 5.19 days p < 0.05). The mean number of debridement sessions was 3.74 ± 0.69 in group 1 versus 1.82 ± 0.34 in group 2. Conclusions: Early exploration and debridement in equivocal (early) FG has a better clinical outcome with reduced hospital stay and number of debridement sessions than conservative treatment with delayed debridement.